Turkish Compliance and Adaptation of EULAR 2013 Recommendations for the Management of Rheumatoid Arthritis with Synthetic and Biological Disease-Modifying Antirheumatic Drugs: Expert Opinion of TLAR - Ataman, Sebnem; Surmeli, Zuhre Sari; Sunar, Ismihan; Ozdemirel, Erhan; AKINCI, AYŞEN; Bodur, Hatice; AKGÜL, ÖZGÜR; ALTAN İNCEOĞLU, LALE; ALTAY, ZÜHAL; Ayhan, Figen; BİRTANE, MURAT; Soy Bugdayci, Derya; et al. (My University, 2015)
Objectives: This study aims to report Turkish League Against Rheumatism-s assessment on the compliance of European League Against Rheumatism 2013 treatment recommendations for rheumatoid arthritis with practices in Turkish rheumatology clinics and adaptations for Turkey.